Correlates of Depression in First-Year College Students - Villatte, Aude; Marcotte, Diane; Potvin, Alexandra (Canadian Journal of Higher Education, 2017)
This study aimed to identify and rank the personal, family-related, social, and academic correlates of depressive symptoms in first-year college students. A questionnaire that included the Beck Depression Inventory-II (BDI-II) was administered to 389 first-year college students (mean age = 18.9; SD = 3.38; 59.4% female). Eight variables contributed uniquely to the variance of depressive symptoms and were, in decreasing order of importance: (1) the absence of personal goals, (2) a high level of anxiety and (3) of dysfunctional thoughts regarding success, (4) a lack of emotional adjustment to college, (5) being female, (6) receiving little warmth and encouragement of autonomy from one’s mother and (7) from one’s father, and (8) being attracted to members of the opposite or both sexes. These results suggest that a multimodal intervention is required to support students’ mental health.